Assessment of the Natural Radioactivity Levels of Soil Samples in IT1 Oil Reservoirs in Kirkuk City, Northeast Iraq - Kareem, Dunya O.; Tawfiq, Nada F. (Iraqi Journal of Physics, 2023)
In this study, gamma-ray spectrometry with an HPGe detector was used to measure the specific activity concentrations of 226Ra, 232Th, and 40K in soil samples collected from IT1 oil reservoirs in Kirkuk city, northeast Iraq. The “spectral line Gp” gamma analysis software package was used to analyze the spectral data. 226Ra specific activity varies from 9  0.34 Bq.kg-1 to 17  0.47 Bq.kg-1. 232Th specific activity varies from 6.2  0.08 Bq.kg-1 to 18  0.2 Bq.kg-1. 40K specific activity varies from 25  0.19 Bq.kg-1 to 118  0.41 Bq.kg-1. The radiological hazard due to the radiation emitted from natural radionuclides in soil samples was also assessed. The average values of the radium equivalent (Raeq), external hazard index (Hex), internal hazard index (Hin), gamma index (I), absorbed dose rate (D), outdoor (AEDEout) and indoor (AEDEin) annual effective dose equivalent were 35.391 Bq.kg-1, 0.095, 0.128, 0.253, 16.118 nGy.h-1, 0.0197 mSv.y-1, and 0.0790 mSv.y-1, respectively. All values obtained for the activity concentrations for 226Ra, 232Th, and 40K and the radiological hazard were lower than the global values. This indicates that no harmful radiation effects are posed to the population who work and live near the study area.